Sorafenib tosylate inhibits autophagy, proliferation and migration of oral squamous cell carcinoma - XIONG Jianzhe; ZHANG Hao; YU Wei (Kouqiang hemian waike zazhi)
[Objective:] To study the effect of Sorafenib tosylate (ST) on autophagy, proliferation and migration of CAL-27 cells in oral squamous cell carcinoma (OSCC). [Methods:] The CAL-27 cells were treated with different concentrations of ST, and their proliferation activity was detected by CCK-8 and cell clone formation assay; the effect of the CAL-27 cells migration was detected by cell wound scratch assay; the expressions of Beclin1, LC3B and PCNA were detected by western blotting. The CAL-27 cells were pretreated with the autophagy activator rapamycin, and the effects of ST on the proliferation, migration and expression of Beclin1, LC3B and PCNA in CAL-27 cells were detected after activation of autophagy. [Results:] Compared with the control group, ST significantly inhibited the proliferation and migration of the CAL-27 cells. ST decreased the expressions of Beclin-1, PCNA and increased the expressions of the cytoplasmic form LC3Ⅰ and the lipid form LC3Ⅱ of LC3B. However, when the CAL-27 cells were pretreated with RA to activate autophagy, the inhibitory effect of ST on proliferation and migration of the CAL-27 cells were weakened, the expressions of Beclin-1 and PCNA were increased, and the expressions of the cytoplasmic form LC3Ⅰ and the lipid form LC3Ⅱ of LC3B were decreased. [Conclusion:] ST may inhibit the proliferation and migration of CAL-27 cells by down-regulating Beclin-1, and inhibiting autophagy. Inhibition of autophagy may be a potential therapeutic strategy for OSCC.